IATO: a flexible EPIC simulation environment - Darsch, A.; Seznec, A. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2004)
High-performance superscalar processors are designed with the help of complex simulation environment. The simulation infrastructure permits to validate the processor instruction set and contributes as well to the performance evaluation of the selected microarchitecture. Unfortunately, new architectures like the EPIC are not properly supported in the research community. Due to its specificity, the EPIC architecture requires a new framework that gives the researcher an opportunity to explore the EPIC paradigm by characterizing the static and dynamic behavior of binary programs. In particular, this task is made difficult by the fact that the EPIC architecture defines a fully predicated ISA. This paper presents a novel simulation infrastructure, called IATO that permits to analyze, emulate and simulate the EPIC microarchitecture by using the IA64 ISA as the reference architecture. The novelty of the environment is to provide an in-order and an out-of-order cycle accurate execution-driven simulators. In particular, the out-of-order simulator provides an innovative solution for the out-of-order execution of a fully predicated ISA.